Sister haplotypes and recombination disequilibrium: a new approach to identify associations of haplotypes with complex diseases - Liao, Shun-Yao; Tan, Yuan-De (Frontiers in Genetics, 2024)
Haplotype-based association analysis has several advantages over single-SNP association analysis. However, to date all haplotype-disease associations have not excluded recombination interference among multiple loci and hence some results might be confounded by recombination interference. To address this issue, we developed a new and robust method for identifying haplotype-disease associations. This method was a sister-haplotype approach based on recombination disequilibrium (RD). Sister haplotypes are determined by translating DNA base language to genotype language. After performing RD tests in control and case cohorts, one can construct a two-by-two contingency table with sister haplotypes and a disease and perform Chi-square test for the association between haplotypes and a complicated disease of study. Applying this method to a haplotype dataset of Alzheimer disease (AD), association of sister-haplotypes containing ApoE3/4 with risk for AD was identified without RD. Haplotypes within genes IL-13 were not associated with risk for breast cancer in the case of no RD and no association of haplotypes in IL-17A gene with risk for coronary artery disease were detected without RD. The previously reported associations of haplotypes within these genes with risk for these diseases might be due to strong RD and/or inappropriate haplotype pairs.